The Changing Faces of Jesus - Lim, Timothy H. (Journal of Semitic studies, 2002)
The Changing Faces of Jesus GezaVermes Allen Lane, The Penguin PressLondon 2000273Hardback£18.99 0‐713‐99193‐3 , 1University of Edinburgh